2019
DOI: 10.1044/2018_jslhr-l-18-0222
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective Experience of Inner Speech in Aphasia Is a Meaningful Reflection of Lexical Retrieval

Abstract: Purpose: Individuals with aphasia often report that they feel able to say words in their heads, regardless of speech output ability. Here, we examine whether these subjective reports of successful "inner speech" (IS) are meaningful and test the hypothesis that they reflect lexical retrieval. Method: Participants were 53 individuals with chronic aphasia. During silent picture naming, participants reported whether or not they could say the name of each item inside their heads. Using the same items, they also com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…We found significant relationships between item-level reports of successful IS during silent picturenaming and accuracy/error type on a spoken naming task in a small group of individuals with aphasia (Hayward, 2016;Hayward et al, 2016). Using similar methods, we then replicated these findings in a larger participant group, again showing that self-reported IS is closely related to lexical retrieval (Fama et al, 2019). These same studies also revealed preliminary evidence that IS does not relate to post-lexical output processing.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…We found significant relationships between item-level reports of successful IS during silent picturenaming and accuracy/error type on a spoken naming task in a small group of individuals with aphasia (Hayward, 2016;Hayward et al, 2016). Using similar methods, we then replicated these findings in a larger participant group, again showing that self-reported IS is closely related to lexical retrieval (Fama et al, 2019). These same studies also revealed preliminary evidence that IS does not relate to post-lexical output processing.…”
Section: Introductionsupporting
confidence: 62%
“…These same studies also revealed preliminary evidence that IS does not relate to post-lexical output processing. Self-reported IS related to word features primarily associated with retrieval, but did not relate to the articulatory complexity of words (Fama et al, 2019;Hayward, 2016). In a separate line of research using an interview-based approach, we found that the experience of successful IS in the specific context of anomia (where successful IS is followed by a failure of spoken output) relates to phonological output processing and to lesions in left ventral sensorimotor cortex (Fama, Hayward, Snider, Friedman, & Turkeltaub, 2017).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations